Trend of STEM Research on Scientific Literacy Skills: A Bibliometric Analysis Using Scopus Database - Fatimah, Siti; Sutikno, Sutikno; Indriyanti, Dyah Rini (Proceeding International Conference on Religion, Science and Education, 2024)
The aim of this research is to identify trends in STEM research related to scientific literacy skills over the years, visualize the research trends in STEM and its impact on scientific literacy skills, and analyze the contribution of STEM research and scientific literacy skills to education in Indonesia. The research data was collected in September 2023 using the Scopus database. The search keywords used in the Scopus database were "STEM Education" OR "STEM Learning" OR stem OR "STEM research" AND "literacy scientific skill" OR "literacy scientific" OR "scientific literacy" OR "science literacy" in multiyears. The data obtained included a total of 267 documents. After analyzing the data, 105 relevant documents were identified. These documents were analyzed using VOSViewer and Biblioshiny. The research findings indicate a strong connection between STEM education and scientific literacy skills. In terms of document types, articles from education science journal and the Jurnal Pendidikan IPA Indonesia were the most prominent sources compared to other document sources. Furthermore, in terms of countries, the United States made the most significant contributions to this topic, with Indonesia ranking second. The University of Alabama at Birmingham was the most prolific affiliate in producing documents on this topic. An intriguing discovery is that STEM education and scientific literacy skills have a substantial impact on education in Indonesia, suggesting the need for further research on this topic.